2015
DOI: 10.1039/c5sc00457h
|View full text |Cite
|
Sign up to set email alerts
|

Et3B-mediated two- and three-component coupling reactions via radical decarbonylation of α-alkoxyacyl tellurides: single-step construction of densely oxygenated carboskeletons

Abstract: We devised new radical-based two- and three-component coupling reactions of sugar derivatives, and realized one-step construction of contiguously substituted polyol structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 54 publications
(19 reference statements)
2
29
0
Order By: Relevance
“…Next, to explore the scope of the radical coupling reactions, the optimized conditions were applied to four α‐alkoxyacyl tellurides 1 b – 1 e (Table 2). Acyl tellurides 1 b , 1 c / d , and 1 e were easily prepared from d ‐fructose, d ‐ribose, and d ‐tartaric acid derivatives, respectively [4,7a,b] . Upon treatment with 2‐hydroxybenzaldehyde ( 7 a , 3 equiv) in the presence of Et 3 B (5 equiv) and Et 2 AlCl (3 equiv) in CH 2 Cl 2 under air at 25 °C, the radical precursors 1 b – 1 e were transformed into the corresponding α‐alkoxy radicals, which reacted with aldehyde 7 a to afford 8 b – 8 e in 57% to 94% yields.…”
Section: Methodsmentioning
confidence: 99%
“…Next, to explore the scope of the radical coupling reactions, the optimized conditions were applied to four α‐alkoxyacyl tellurides 1 b – 1 e (Table 2). Acyl tellurides 1 b , 1 c / d , and 1 e were easily prepared from d ‐fructose, d ‐ribose, and d ‐tartaric acid derivatives, respectively [4,7a,b] . Upon treatment with 2‐hydroxybenzaldehyde ( 7 a , 3 equiv) in the presence of Et 3 B (5 equiv) and Et 2 AlCl (3 equiv) in CH 2 Cl 2 under air at 25 °C, the radical precursors 1 b – 1 e were transformed into the corresponding α‐alkoxy radicals, which reacted with aldehyde 7 a to afford 8 b – 8 e in 57% to 94% yields.…”
Section: Methodsmentioning
confidence: 99%
“…2:1a tC5). [11,12] Thec ompatibility of the preinstalled nucleobases with the reaction conditions was unknown at this stage, [13,14] but we expected that direct attachment of the a-amino acid portion to 5a-d would streamline the route to 1a-d.…”
mentioning
confidence: 99%
“…Ther adical-exchange reaction between 5a-d/6 and the ethyl radical generated from Et 3 Band O 2 provides the corresponding a-alkoxyacyl radical Aa-d/C.N ext, favorable orbital interactions of the C À CO s*-bond of Aa-d/C with the antiperiplanar oxygen lone pair facilitates ejection of CO to generate Ba-d/D. [11,12,22] Thel ost stereochemical information at the C4' or C3'' position of Ba-d/D is redefined by CÀC bond formation. Thea cetonide methyl group of the 5/5-cisfused bicycle Ba-d,and the siloxymethyl group of monocycle D,block the corresponding top and bottom faces,respectively, thus forcing the approach of oxime 4 from the opposite faces to establish the C4' and C3'' stereocenters.…”
mentioning
confidence: 99%
“…To simplify the synthetic scheme and minimize functional-group transformations,w e decided to extend the multiply functionalized chains of 1a-d from readily accessible ribonucleosides 5a-d containing four different nonprotected pyrimidine rings. [11,12] Thec ompatibility of the preinstalled nucleobases with the reaction conditions was unknown at this stage, [13,14] but we expected that direct attachment of the a-amino acid portion to 5a-d would streamline the route to 1a-d. [10] We recently reported that a-alkoxyacyl telluride 7 and oxime 8 were smoothly assembled into the ribonofuranosyl a-amino acid 9 through Et 3 B/O 2 -promoted decarbonylative radical addition, albeit with low C5 stereoselectivity (d.r.…”
mentioning
confidence: 99%
“…[20] Despite the differences in the C5 substituents on the pyrimidine rings,E t 3 B/O 2 -promoted reactions of 5b, 5c, and 5d successfully attached the a-amino acid structure to yield 2b (64 %), 2c (69 %), and 2d (64 %) in ad iastereoselective fashion with respect to the formation of the C4' and C5' centers.T he same procedure was applied to 6 and 4 (2 equiv) to produce the protected trihydroxynorvaline fragment 3 with complete control of the newly formed C2'',C3'' stereocenters.T hus, 2a-d and 3 were prepared in only four steps from the starting materials 10 a-d and 12,respectively. [11,12,22] Thel ost stereochemical information at the C4' or C3'' position of Ba-d/D is redefined by CÀC bond formation. Ther adical-exchange reaction between 5a-d/6 and the ethyl radical generated from Et 3 Band O 2 provides the corresponding a-alkoxyacyl radical Aa-d/C.N ext, favorable orbital interactions of the C À CO s*-bond of Aa-d/C with the antiperiplanar oxygen lone pair facilitates ejection of CO to generate Ba-d/D.…”
mentioning
confidence: 99%